Antigone in the Americas democracy, sexuality, and death in the settler colonial present - Henao Castro, Andrés Fabián (SUNY series in gender theory., 2021)
Argues for a decolonial reinterpretation of Sophocles' classical tragedy, Antigone, that can help us to rethink the anti-colonial politics of militant mourning in the Americas.